Developing “synchronous model” in english teaching material for public health students: a systematic literature review - Syakur, Abd.; Nyoman Padmadewi, Ni; Prasetya, Rizki; Prawoco, Fajar Sandi (International Journal of Research in Counseling and Education, 2023)
The Synchronous Model has become an important part of the development of learning in the 4.0 era. Online learning for teaching English has become a trend that continues to grow and is developed based on the development of Special English (ESP). The Synchronous Model is a media model developed by researchers as the website Synchronous which has been popular in Indonesia and is being developed. However, this review of the Synchronous Model learning in ESP is still relatively rarely developed in the post-pandemic period, preparing rich and reliable Synchronous technology-based learning that is very meaningful and reliable in the future. This technology enhances the scientific nature of English language education in public health at colleges and at the university level. So, this review systematically identifies trends in Synchronous-based learning in ESP for Public Health courses. Data tracking in this study was conducted using Harzing’s Publish or Perish (PoP) application with three databases used, including Google Scholar (GS), Crossref, and Scopus. From the results of the data screening, 6 articles were found that met the inclusion and exclusion criteria. The conclusion obtained from this systematic search is that the Synchronous Model is the most widely used model in the process of learning English specifically. Second, the Synchronous Model and language are more widely used in ESP learning for public health. Third, the Synchronous Model in ESP dominates the learning process after the Covid-19 pandemic. These three findings imply that there are still gaps in the Synchronous Model and ESP research. In general, this review is very valuable for practitioners to find out which Synchronous Model is ready to be used and developed and can identify gaps for research in Public Health (ESP) English language learning, this SLR is very closely integrated into technology-based learning with English language education in public health at the college and university level.